PERANCANGAN INTERIOR KLINIK KECANTIKAN ERHA DERMA CENTER DENGAN KONSEP MODERN KONTEMPORER DI TANGERANG - Cindylaras, Nadya; Astuti, Anggi Dwi (Anggada : Jurnal Desain dan Seni, 2021)
Healthy skin can add value to appearance. Therefore, there are various beauty clinics. Beauty clinic is a place that provides services in the field of care and also skin beauty. Erha Clinic provides complete services, from facial skin, body to scalp and hair.Interior design in a beauty clinic is needed to adapt the facilities to existing needs, in addition interior design can attract attention and provide comfort to visitors on public buildings care and health of the body. Interior design with Modern concept according to (Khoirunis, 2016) is a popular design style in the 1900s with neutral color characteristics, clean, and minimal decoration or decoration. While the contemporary concept according to Theory (Wibawa, 2017) is a design refers to a more sophisticated interior decoration. Contemporary here will put more emphasis on the green era of design. Green design is synonymous with energy saving and design that cares about the environment, both in terms of materials and multiplying wall openings, in order to save electricity and create fresh space. Facilities that will be designed include treatment rooms, consulting rooms, receptionists, and waiting rooms. The theme is "Modern Contemporary Style with a Natural Look" and the atmosphere of the room to be built is clean as the characteristics of the clinic, Warm, Natural, Releks and safe. This theme is also adapted to the pandemic conditions faced at this time to prevent the transmission of the COVID-19 virus by implementing government policy regulations on COVID-19.